Antibacterial Activity of Euphorbia tirucalli against Lactobacillus acidophilus: An In Vitro Study - Bang, Vania Christina Budiono; Hapsari, Rebriarina; Kusuma, Ira Anggar (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
Dental caries is a common oral disease that occurs due to excessive interaction between tooth structure, bacterial biofilm, and glucose. Lactobacillus acidophilus is the main cause of dentin dental caries, which can be prevented using anticaries agents. However, current anticaries agents may cause some side effects. Therefore, there is a need for natural anticaries agents with minimal side effects. Euphorbia tirucalli contains flavonoids, tannins, and saponins that contribute to its antibacterial activity. This study aimed to determine the antibacterial activity of E. tirucalli against L. acidophilus bacterial growth. This was an in-vitro study with a post-test-only control group design, divided into three groups. The positive control group received 0.2% chlorhexidine digluconate, the negative control group received aquadest, and the intervention groups received extracts with concentrations of 10 mg/mL, 20 mg/mL, 30 mg/mL, 40 mg/mL, and 100 mg/mL. Minimum Inhibitory Concentration (MIC) was examined post-treatment using the agar dilution method. The differences in colony growth were analyzed using Cramer's V and Fisher's Exact Test, with p<0.05 considered significant. E. tirucalli extracts showed antibacterial effects against L. acidophilus with a concentration of 40 mg/mL as the MIC. Extract groups with concentrations of 40 mg/mL and 100 mg/mL showed significant differences in L. acidophilus growth compared to the negative control group (p<0.001). The study concluded that E. tirucalli extract has antibacterial activity against the growth of L. acidophilus, with MIC of 40 mg/mL.